Directly grown TiO2 nanotubes on carbon nanofibers for photoelectrochemical water splitting. Issue 46 (24th May 2016) - Han, Hyungkyu; Kment, Stepan; Goswami, Anandarup; Haderka, Ondrej; Zboril, Radek
ABSTRACT: A variety of Titanium dioxide (TiO2 ) phases and nanostructures have been explored for their applications in photoelectrochemical cells (PECs) for solar-driven water splitting. In this case, anatase phase and TiO2 nanotubes offer significant advantages especially for PEC-based applications. Though, significant efforts have already been engaged to combine the advantages from both the fields, poor activation and the high electron-hole pair recombination rate of TiO2 electrodes, originating from intrinsic physicochemical properties, limits its practical use. As an alternative, we report directly grown TiO2 nanotubes (synthesized on Fluorine doped Tin Oxide (FTO) via facile electrospinning technique) on carbon nanofibers, using hydrothermal method. The hierarchical branch type configuration has an intimate contact between the TiO2 nanotube and carbon nanofiber backbone and offers higher photocatalytic activity than their respective individual components (namely TiO2 nanotubes and carbon nanostructures).